2008
DOI: 10.1007/s10750-008-9581-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope and fatty acid tracers in energy and nutrient studies of jellyfish: a review

Abstract: Studies of the trophic ecology of gelatinous zooplankton have predominantly employed gut content analyses and grazing experiments. These approaches record only what is consumed rather than what is assimilated by the jellyfish, only provide evidence of recent feeding, and unless digestion rates of different prey are known, may provide biased estimates of the relative importance of different prey to jellyfish diets. Biochemical tracers, such as stable isotopes and fatty acids, offer several advantages because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…For nitrogen, fractionation is larger and on average 3.5 ‰ per trophic level (McCutchan et al 2003, Waddington & MacArthur 2008. Fractionation rates can vary between species with such issues as diet type (Vanderklift & Ponsard 2003) and dietary studies are required to confirm the fractionation rates of individual species (Pitt et al 2009). As this was beyond the scope of the present study, the sensitivity of the IsoSource mixing model was run for each species using a range of fractionation rates for carbon and nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For nitrogen, fractionation is larger and on average 3.5 ‰ per trophic level (McCutchan et al 2003, Waddington & MacArthur 2008. Fractionation rates can vary between species with such issues as diet type (Vanderklift & Ponsard 2003) and dietary studies are required to confirm the fractionation rates of individual species (Pitt et al 2009). As this was beyond the scope of the present study, the sensitivity of the IsoSource mixing model was run for each species using a range of fractionation rates for carbon and nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the isotopic separation of algal species, or the detection of a proportional change to lobster diet (in response to changes in lobster density) is difficult in situations where lobsters are consuming a wide range of food items from differing trophic levels. δ 15 N values can also be influenced by diet quality (Vander Zanden & Rasmussen 2001) and can vary between the tissue types of the target species (Pitt et al 2009). Manipulative feeding trials were beyond the scope of the present study but may help to calibrate the feeding relationships indicated by stable isotopes in the present context.…”
Section: Resolution Of Chemical Tracers and Lobster Dietmentioning
confidence: 99%
“…ctenophores) are diYcult to quantify and identify owing to fast deterioration in the oral arms and gut cavity (Båmstedt and Martinussen 2000;Ishii and Tanaka 2001;Pitt et al 2009); (2) once out of the water, gelatinous samples rapidly lose physical integrity; (3) sampling at remote sites or on research cruises of extended duration can limit access to suitable processing/analytical equipment and jellyWsh collected in the Weld are typically preserved by freezing or storage in ethanol (EtOH) (Hobson et al 1997). Preservation methods employed prior to stable isotope analysis (SIA) have been shown to alter isotopic composition in a range of marine taxa ranging from algae (Kaehler and Pakhomov 2001;Carabel et al 2009) through to invertebrates (Bosley and Wainwright 1999;Kaehler and Pakhomov 2001;Carabel et al 2009) and higher vertebrates (Bosley and Wainwright 1999;Kaehler and Pakhomov 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, although we were able to provide some data on the biomass of stranded jellyfish that this is only a reflection of the total biomass as we do not know what percentage of the population is stranded at any one time. Other jellyfish species which undergo swarms have been shown to be important in delivering significant quantities of organic matter into coastal food webs (Pitt et al, 2009b;West et al, 2009). Kramp (1961) records C. mastigophora as reaching 400 mm in diameter, but our specimens were almost all less than half this size.…”
Section: Distribution and Occurrence Of Swarmsmentioning
confidence: 74%